Balkan Ekspres - Baletić, Branko (Yugoslavia : Art Film Beograd ; Inex Film Beograd, 1983)
This madcap comedy, set in the last days before the German invasion of Yugoslavia in April 1941, follows the adventures of a group of petty-thieves, wandering around disguised as the music ensemble called “Balkan Express.” They find plenty of opportunities to practice their trade amidst the confusion which erupts everywhere as people flee the invading Nazis. However, when the Nazis actually move in, things take a turn for the worse and the group's only concern now is to stay alive under the first horrors of the war. Through chance and necessity, these people from the dregs of society grow out of their meaningless destinies and become unlikely war heroes . The film was a great success thanks to its unprecedented comic treatment of the mythic partisan struggle during WWII, and was soon followed by a sequel focusing on the same group of characters.
Duration: 01:28:00
Keywords: Fiction films